P262 Clinico- microbiological profile of post-COVID pulmonary fungal infections encountered during the second wave of COVID-19 pandemic at a tertiary care teaching hospital in the Himalayas. (20th September 2022) - Puri, Oshin; Bhatia, Mohit; Rekha, U Sasi; Chakraborty, Deepika; Dua, Ruchi; Dhar, Minakshi; Chauhan, Udit; Prasad, Amber; Kalita, Deepjyoti; Kaistha, Neelam
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objective: The study aims to generate preliminary data about post-COVID pulmonary fungal infections in the Himalayas and analyze patients' micro-radio-clinical profiles and outcomes. Methodology: We conducted a retrospective study at a tertiary care teaching hospital in the Himalayas to generate preliminary post-COVID pulmonary fungal infection data. Sputum, Endotracheal Tube (ET), and Bronchoalveolar lavage (BAL) samples of patients sent to the Mycology laboratory were subjected to KOH mount and aerobic inoculation on Sabouraud dextrose agar plates at 37 ° C. The patients' symptoms, diagnosis, clinical-radiological profile, and outcome were collected from the hospital database. Results: Among n  = 16 cases of post-COVID pulmonary fungal infections aged 53 +/- 13.38 years, n  = 7 (43.75%) had Pulmonary Aspergillosis ( n  = 5 A. fumigatus, n  = 1 A. flavus, n  = 1 A. niger ), n  = 5 (31.25%) had Pulmonary Mucormycosis ( Rhizopus arrhizus ), and n  = 4 (25%) had mixed infection. In 2 of 4 mixed infection patients, R. arrhizus was identified on KOH microscopy and A. fumigatus on SDA Agar. Both A. fumigatus and R. arrhizus were identified on KOH Microscopy of the third patient, while only A. fumigatus was cultivated on his SDA Agar. Aspergillus flavus and R. arrhizus were isolated simultaneously from the sample of the last patient, but only R. arrhizus was identified on KOH Microscopy. Clinical symptoms were similar among Pulmonary Aspergillosis and Mucormycosis patients, but hemoptysis was reported only among Pulmonary Aspergillosis patients. Pre-existing co-morbid end-organ damage, AKI, CKD, CLD, COPD, and CAD was more common among Pulmonary Mucormycosis patients and rare among Pulmonary Aspergillosis patients. Treatment requirements and clinical outcomes of patients infected with either mold were similar. The clinical profile of mixed infection patients was notably different from the others. All the patients were males, none complained of chest pain or expectoration, and none had a history of PTB, AKI, CKD, CLD, COPD, or CAD. Only 2 (50%) mixed infection patients needed supplemental high flow oxygen, unlike all (100%) patients diagnosed with single mold infection. None of the mixed infection patients required steroids. Moreover, none of the mixed infection patients died, unlike 60% mortality in cases of single-species infections. On radiological investigation, n  = 6 had typical thick-walled cavitary lesions with air-fluid levels and multiple centrilobular nodules giving a tree in bud appearance, of which n  = 4 had bilateral lung involvement, and n  = 2 had only one lung involved. n  = 1 patient had a well-circumscribed lung abscess. Conclusion: COVID patients from the Himalayas had a higher prevalence of invasive pulmonary fungal infections, probably due to the dense surrounding vegetation. The immuno-compromised state following COVID-19 infection/treatment might be responsible for the progression of regular exposure to invasive pulmonary infection.